Selecting the most appropriate corrective actions for energy saving in existing buildings A/C in hot arid regions - Al-Widyan, Mohamad I.; Al-Oqla, Faris M. (Building simulation, 2014)
Energy consumption, especially by the A/C load, represents a major concern particularly in hot arid regions. Selecting the best energy saving option under these conditions is a function of many various variables and thus represents a multi-criteria decision making problem. This study involved building a decision-making model to specify the most important and adequate alternatives to energy conservation in cooling systems in existing buildings in hot arid regions. It examined the best corrective action(s) to be implemented based on a number of criteria that were subject to weighting by experts. The energy saving corrective action options considered were limited to Providing Sufficient Thermal Insulation, Changing Occupant’s Habits, Providing Appropriate Shading, Building Tightness (sealing air leakage), Use of Modern Controllers, and Use of Efficient Equipment. The Analytical Hierarchy Process (AHP) along with its commercial software package, EXPERT CHOICE™, were utilized in this study. The findings of the study indicated that under normal conditions, both Providing Appropriate Shading and Building Tightness represent the best choices of energy saving actions in hot arid regions and that the AHP provides a powerful analysis tool that leads to consistent judgment and reliable decision. In fact, the method demonstrated itself as a fundamental knowledge-based tool that enables quantifying and analyzing experts’ qualitative judgments that lead to sound multi-criteria decision making.